2001
DOI: 10.1007/s002210100819
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive control of cyclical bimanual forearm movements across different movement frequencies as revealed by means of tendon vibration

Abstract: The effect of unilateral tendon vibration on the performance of cyclical bimanual forearm movements was investigated across different cycling frequencies (from 0.67 to 2.53 Hz). The spatiotemporal features of the individual limb motions as well as their coordination were studied. Tendon vibration was found to result in a substantial reduction in the amplitude of the vibrated arm, leaving the nonvibrated arm unaffected. The vibration-induced amplitude reduction decreased from 26% to 11% as cycling frequency inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
5
10
0
Order By: Relevance
“…Stated differently, the reliance on proprioception in performance was evident not only during the performance of the "non-stable" anti-phase patterns but also in the "stable" in-phase patterns, suggesting that bimanual coupling appears to be controlled, for the main part, by proprioceptive information. These findings are largely supported by previous studies where proprioception was either absent [23] or masked [17,26,34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Stated differently, the reliance on proprioception in performance was evident not only during the performance of the "non-stable" anti-phase patterns but also in the "stable" in-phase patterns, suggesting that bimanual coupling appears to be controlled, for the main part, by proprioceptive information. These findings are largely supported by previous studies where proprioception was either absent [23] or masked [17,26,34].…”
Section: Discussionsupporting
confidence: 88%
“…The present study also shows that the triceps and anterior deltoid muscle vibration lead to reducing the amplitude of the drawing circles. The vibration of the wrist flexor tendon destroys coordination between the two hands [10,17,34]. This result shows that proprioceptive information plays an essential role in the central nervous system for keeping posture [17].…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced stability might be a general feature of the advanced balance skill exhibited by dancers, as dancers have exhibited enhanced neuromuscular responses and proprioceptive sensitivity [1][2][3][4][5][6]. It is unclear whether greater postural coordination stability might be associated with speed of neuromuscular responses, but research does suggest these stability results could be related to enhanced proprioceptive sensitivity [16][17][18][19]. The tracking task entails proprioceptive feedback to establish and maintain reciprocal, functional linkages between the various muscles and joints and our results are consistent with the hypothesis of a direct relation between proprioceptive sensitivity and coordination stability, although this must be further examined.…”
Section: Discussionmentioning
confidence: 94%
“…2 This sensitivity should associate with greater coordination stability, as proprioception is known to play an important role in the establishment of linkages among components of coordinative structures thereby enhancing neuromuscular control, particularly in multi-joint coordination [16][17][18][19]. We tested this hypothesis by requiring participants to stand on a single leg rather than bi-pedally to increase task demands, as previous results indicated that differences between experts and controls may not be apparent when postural demands are minimal [9].…”
mentioning
confidence: 90%
“…Interestingly, the affected arm was unimpaired in unimanual tasks [5]. In bimanual rhythmic circling movements, vibratory stimuli increased the normal delay between the leading dominant hand and the non-dominant hand [11].…”
Section: Data Acquisitionmentioning
confidence: 98%